Interferential current stimulation enhances rectal motor activity: insights from an isolated perfused porcine model - Martel, Richard; Boettcher, Michael; Klinke Petrowsky, Michaela; Hoyos Celis, Nicolas Andres; Herrmann, Irmgard; Magerl, Walter; Herrmann, Martin (European journal of pediatric surgery, 2025)
Introduction: Interferential current (IFC) has been studied in several clinical trials for the treatment of bowel motility disorders, most often in children. However, only moderate effects are reported, and in contrast to IFC, the so-called placebo application is indiscernible. The mechanisms and neuroanatomic points of action remain elusive. Therefore, this therapy remains being questioned. Methods: To gain objective experimental data about IFC stimulation, we examined this method ex vivo in an isolated perfused porcine rectum including the mesorectum. To elucidate the role of plexus nerve fibers and enteric ganglia, we performed IFC stimulation also in the presence of tetrodotoxin (TTX) or hexamethonium (HXN). We applied the commonly used stimulation modes with a beat frequency sweeping between 5 and 25 Hz (IFCd5-25) and 80 and 150 Hz (IFCd80-150). We monitored intraluminal pressure and motility by online barometry and video recording, respectively. Motor activity, reflected by changes in the intraluminal pressure (cm H2O·s−1) and longitudinal movements (pixels·s−1), was quantified over time as root mean squares (RMSs). Results: After IFCd5-25, we observed a 30% increase in the rectal motility in the pressure changes which was sustained over 30 minutes post-stimulation (p < 0.02); only a minor effect was detected for IFCd80-150. Both TTX and HTX abolished the stimulation. This suggests neuronal modulation. Conclusion: IFCd5-25 stimulates rectal motor activity in the isolated perfused porcine rectum. Ganglia in the enteric nervous system are modulated to allow increased activity for at least 30 minutes. Therefore, the isolated porcine rectum is a suitable tool to study the effectiveness of various IFC settings in the rectum.
Artikel online veröffentlicht: 11. Dezember 2024
Gesehen am 13.03.2025